2006
DOI: 10.1127/0003-9136/2006/0165-0557
|View full text |Cite
|
Sign up to set email alerts
|

Nonrandom mating, mate choice, and male-male competition in the crayfish Austropotamobius italicus, a threatened species

Abstract: Abstract:The omnivorous habit and food selection in freshwater macroinvertebrates was investigated in the white-clawed crayfish, Austropotamobius pallipes, a threatened species. First, during an annual cycle we analysed gut contents for vascular plant detritus, moss, amorphous plant material, and animal remains, and evaluated their organic content. Second, we ran preference experiments in the laboratory, in which crayfish had to choose, in the first trial among three vegetal items, in the second trial among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
(41 reference statements)
1
17
0
Order By: Relevance
“…Females with the opportunity to mate in both mating seasons had the highest possibility of selecting the best mates or collecting spermatophores from the maximum number of males. Mechanisms of sexual selection in crayfish have been described [47], [48], [49], but it is unclear whether females can strictly limit mating only to the best males. In addition, the number of males from which a female can store the spermatophores is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Females with the opportunity to mate in both mating seasons had the highest possibility of selecting the best mates or collecting spermatophores from the maximum number of males. Mechanisms of sexual selection in crayfish have been described [47], [48], [49], but it is unclear whether females can strictly limit mating only to the best males. In addition, the number of males from which a female can store the spermatophores is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Gwynne, 1981), in spiders (Uhl, 1998) and in a few non-decapod crustaceans (gammarid amphipods, Elwood, Gibson & Neil, 1987;isopods, Ridley & Thompson, 1979), but, except in the spiny lobsters (MacDiarmid & Butler, 1999), it has never been demonstrated in decapods (see, e.g. Villanelli & Gherardi, 1998;Gherardi et al, 2006). The only indirect evidence comes from Rubolini et al (2006), who showed the ability by male Au.…”
Section: Mate Choice By Malesmentioning
confidence: 99%
“…In the majority of the species studied so far, large males are successful when competing with other males for access to females (Jennisons & Blackwell, 1996). Large crayfish males are dominant over smaller ones (Berrill & Arsenault, 1984;Villanelli & Gherardi, 1998) and more easily force females to copulate (Snedden, 1990;Gherardi et al, 2006). However, the advantage of large males outcompeting other males or coercing females does not necessarily imply a female preference for large males, as found in the present study and suggested for other crayfish species (Austropotamobius italicus Gherardi et al, 2006; Cherax quadricarinatus Barki & Karplus, 1999).…”
Section: Mate Choice By Femalesmentioning
confidence: 99%
See 2 more Smart Citations